Hemoglobin Changes After Long-Term Intermittent Work at High Altitude - Akunov, Almaz; Sydykov, Akylbek; Toktash, Turgun; Doolotova, Anara; Sarybaev, Akpay (Frontiers in Physiology, 2018)
Chronic high altitude hypoxia leads to an increase in red cell numbers and hemoglobin concentration. However, the effects of long-term intermittent hypoxia on hemoglobin concentration have not been studied. The aim of this study was to evaluate hemoglobin levels in workers commuting between an elevation of 3,800 m (2-week working shift) and lowland below 1,700 m (2 weeks of holiday). A total of 266 healthy males, aged from 20 to 69 years (mean age 45.9 ± 9.3 years), were included into this study. The duration of intermittent high altitude exposure ranged from 0 to 21 years. Any cardiac or pulmonary disorder was excluded during annual check-ups including clinical examination, clinical lab work (blood cell count, urine analysis, and biochemistry), ECG, echocardiography, and pulmonary function tests. The mean hemoglobin level in workers was 162 ± 16 g/L. Simple linear regression revealed an association of the hemoglobin levels with the duration of intermittent high altitude exposure. Hemoglobin levels increased 0.68 g/L [95% CI: 0.36 to 1.0, p < 0.001] for every year of intermittent high altitude exposure. Further, after adjusting for other confounding variables (age, living at low or moderate altitude, body mass index, and occupation) using multivariate regression analysis, the magnitude of hemoglobin level changes decreased, but remained statistically significant: 0.46 g/L [95% CI: 0.06 to 0.87, p < 0.03]. We concluded that hemoglobin levels have a statistically significant linear relationship with the duration of intermittent high altitude exposure.